Drug‐induced alloreactivity: A new paradigm for allorecognition. Issue 9 (17th June 2019) - D'Orsogna, Lloyd J.; Almeida, Coral‐Ann M.; van Miert, Paula; Zoet, Yvonne M.; Anholts, Jacqueline D. H.; Chopra, Abha; Watson, Mark; Witt, Campbell; John, Mina; Claas, Frans H. J.
Abstract : Abacavir administration is associated with drug‐induced hypersensitivity reactions in HIV+ individuals expressing the HLA‐B*57:01 allele. However, the immunological effects of abacavir administration in an HLA‐B57 mismatched transplantation setting have not been studied. We hypothesized that abacavir exposure could induce de novo HLA‐B57‐specific allorecognition. HIV‐specific CD8 T cell clones were generated from HIV+ individuals, using single cell sorting based on HIV peptide/HLA tetramer staining. The T cell clones were assayed for alloreactivity against a panel of single HLA‐expressing cell lines, in the presence or absence of abacavir. Cytokine assay, CD137 upregulation, and cytotoxicity were used as readout. Abacavir exposure can induce de novo HLA‐B57 allorecognition by HIV‐specific T cells. A HIV Gag RK9/HLA‐A3‐specific T cell did exhibit interferon‐γ production, CD137 upregulation, and cytolytic effector function against allogeneic HLA‐B57, but only in the presence of abacavir. Allorecognition was specific to the virus specificity, HLA restriction, and T cell receptor TRBV use of the T cell. We provide proof‐of‐principle evidence that administration of a drug could induce specific allorecognition of mismatched HLA molecules in the transplant setting. We suggest that HIV‐seropositive recipients of an HLA‐B57 mismatched graft should not receive abacavir until further studies are completed. Abstract : Using single cell sorted HIV‐specific T cell clones and single HLA transfected cell lines, the authors provide proof‐of‐principle evidence that exposure to a drug could induce pre‐existing virus‐specific memory T cells to crossreact against allogeneic HLA molecules in a transplant setting.